Project Conversion of Electrostatic Precipitator (ESP) Raw Mill To Bag House Filter (BHF) Indrarung IV PT. Semen Padang - Putra, Irwan Kartadi; Putri, Nilda Tri (Journal of Energy and Electrical Engineering, 2024)
The cement industry is one of the largest contributors to air pollution due to its high level of energy consumption. Emissions from cement factories contain chemicals that are harmful to health and the environment. Electrostatic Precipitator (ESP) is a dust collector commonly used in cement factories. As a result of the lifetime of the equipment being more than 30 years, the reliability of the ESP for collecting dust has decreased. In normal operation, ESP emits stack emissions ± 40 mg/Nm3 and can reach more than 60 mg/Nm3 under abnormal conditions.To reduce the impact of emissions on the environment, reduction efforts are needed so that dust emissions in chimneys according emission standards, both during normal and abnormal operating conditions. To overcome the limitations of ESP performance, conversion to Bag House Filter (BHF) was carried out. After the conversion was carried out, the emission level that came out of the chimney was 9 mg/Nm3. With BHF's high ability and efficiency in collecting dust, chimney emissions can be reduced by 78%. Keywords: Bag House Filter, Electrostatic Precipitator, Emission